Molecular docking of triterpenoids from Neem with the ecdysone receptor of lepidopteran pests (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
An in silico docking study was performed to evaluate the interaction of various triterpenoids present in neem with the ecdysone receptor of two economically important lepidopteran pests viz., Helicoverpa armigera (HaEcR) and Plutella xylostella (PxEcR). Twenty triterpenoids were selected for the study, and their docking scores with HaEcR and PxEcR were calculated using the program AutoDock Vina. A commercially available DAH insecticide, tebufenozide, was used as a reference ligand. Out of the twenty triterpenoids used for the study, six and nine triterpenoids recorded binding energy lower than the reference ligand, tebufenozide, when docked with HaEcR and PxEcR, respectively. Four triterpenoids, viz., isomeldenin, azdiradione, 6-deacetylnimbinene, and nimocinol, docked effectively with the ecdysone receptor of both insect pests. In addition, nimbinene and 6-deacetylnimbin also docked effectively with HaEcR and epoxyazadiradione and nimbocinol with PxEcR. Most of the lead compounds were able to form hydrogen bonds with the ecdysone receptor molecule. We found two key amino acid residues, Asn of HaEcR and Ser of PxEcR, at the 504th position, based on their ability to form hydrogen bonds with many lead triterpenoids tested. Other residues, such as Trp 526 in HaEcR and Lys 372 and Phe 520 in PxEcR, were involved in hydrophobic and π-π stacking interactions with many lead triterpenoids, suggesting these residues as an important point of interaction between receptor and ligand molecules. Triterpenoids such as tirucallol, 3-tigloylazadirachtol, and azadirone, although recorded binding energy lower than tebufenozide when docked with PxEcR, failed the prerequisite conditions laid down by Tice rule for a successful pesticide. The lower binding energy of the lead compounds suggests their stable interaction with the receptor molecule and their possible use as an ecdysone agonist or antagonist for effective insect control.